The effects of business credit support programs: Evidence from a regression discontinuity design - Balila Acurio; Alessandro Tomarchio (Graduate Institute of International and Development Studies, 2024)
Government-backed business loan programs have commonly been used as a policy tool for mitigating the impact of adverse scenarios such as the recent pandemic. However, the effects of these policies on micro, small and medium enterprises remain unclear, particularly in developing countries. Using firm-level data and a Fuzzy Regression Discontinuity Design, we studied the impact of a large credit support program deployed in Peru in 2020 (Reactiva Peru'). We examined real outcomes such as employment, sales, and survival. A positive and significant effect of the Reactiva loans on the number of employees was found; this effect continues to linger three years after the pandemic.
Keywords: H81; E26; H32; G20; 330; government-backed loans; regression discontinuity; small and medium-sized enterprises; developing country; business loans; crisis